The properties and durability of autoclaved aerated concrete masonry blocks - A. Chaipanich (2018)
© 2015 Elsevier Ltd All rights reserved. This chapter describes various aspects such as of autoclaved aerated concrete masonry blocks which include the history, utilization, manufacturing process, mechanism, microstructure, characterizations, physical, mechanical, thermal and durability properties. Physical properties section describes the bulk density of autoclaved aerated concrete and the relation to the air voids. The mechanical properties section describes the compressive strength and flexural strength of the autoclaved aerated concrete, the relationships with the physical properties and the hydration products is also discussed. Microstructure section describes the pore size formed and the morphology of the autoclaved aerated concrete microstructure characterized through the use of a scanning electron microscopy. While the other characterization section discusses the phases characterized by means of X-ray diffraction and thermogravimetric analysis techniques. Thermal conductivity is also discussed in the chapter. While the durability section of the chapter describes the freeze-thaw resistance of the autoclaved aerated concrete.